Evaluating new bio-hydrogen producers: Clostridium perfringens strain JJC, Clostridium bifermentans strain WYM and Clostridium sp. strain Ade.TY - Wong, Yee Meng; Wu, Ta Yeong; Ling, Tau Chuan; Show, Pau Loke; Lee, Sze Ying; Chang, Jo-Shu; Ibrahim, Shaliza; Juan, Joon Ching (Elsevier, 2018)
Three newly discovered H2 producing bacteria namely Clostridium perfringens strain JJC, Clostridium bifermentans strain WYM and Clostridium sp. strain Ade.TY originated from landfill leachate sludge have demonstrated highly efficient H2 production. The maximum H2 production attained from these isolates are in the descending order of strain C. perfringens strain JJC > C. bifermentans strain WYM > Clostridium sp. strain Ade.TY with yield of 4.68 ± 0.12, 3.29 ± 0.11, and 2.87 ± 0.10 mol H2/mol glucose, respectively. The result has broken the conventional theoretical yield of 4 mol H2/mol glucose. These isolates were thermodynamically favourable with Gibbs free energy between −33 and −35 kJ/mol (under process conditions: pH 6, 37 °C and 5 g/L glucose). All three isolates favour butyrate pathway for H2 production with the ratio of acetate and butyrate of 0.77, 0.65 and 0.80 for strain JJC, WYM and Ade.TY, respectively. This study reported provides a new insight on the potential of unique bacteria in H2 production.